A composite coating for buildings, its preparation method and use

CN122750201APending Publication Date: 2026-09-15GUANGDONG MUFENG YIJU NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610834192.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-10
Publication Date
2026-09-15

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the technical field of building functional coating, and discloses a composite coating for buildings, a preparation method and application thereof. The composite coating comprises a water-based polymer matrix, a damping elastomer, a heat preservation dispersed phase, a bio-based composite component and water; the bio-based composite component is compounded by eucommia bark extract, silk protein peptide and microbial fermentation extracellular polysaccharide and is pre-emulsified into a stable water dispersion. The bio-based components synergistically form a high-damping viscoelastic structure and a uniform controllable microporous system in the coating film, so that the coating has excellent floor impact sound insulation performance, suitable water vapor permeability and high waterproof and anti-permeability. The prepared coating L n,w (CI) is 62 dB, the water vapor permeability can reach 145 g / (m 2 ·24 h), the maximum impermeable water pressure can reach 0.30 MPa, and can be widely applied to sound insulation and vibration reduction, moisture and water prevention and ventilation protection engineering of building floors and walls.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional building coatings, and more specifically, to a composite coating for building, its preparation method, and its application. Background Technology

[0002] Damping coatings are important functional materials in the construction industry for achieving vibration reduction, noise reduction, thermal insulation, and sound insulation. They can attenuate structural vibrations and block solid-borne sound transmission through viscoelastic energy dissipation, and have been widely used in walls, floors, and roofs.

[0003] Existing architectural damping coatings are mostly prepared by compounding damping components, inorganic fillers, and various additives, using water-based polymer emulsions as the base. For example, CN118064008A discloses a damping coating for buildings, using polybutadiene rubber and polyacrylate as the damping main body, and physically blending it with glass fiber powder, nano silica, and various additives such as mildew inhibitors and waterproofing agents, aiming to give the coating comprehensive properties such as damping, sound insulation, waterproofing, and mildew prevention; CN106947346A discloses a thermal insulation damping coating, using silicone acrylic emulsion as the base, introducing porous cross-linked polymer microspheres and titanium silicate radiation fillers to achieve a combination of thermal insulation and damping noise reduction functions.

[0004] The aforementioned coatings generally suffer from the problem of balancing waterproofing and breathability. To ensure waterproofing, the coating is usually designed with a dense structure, which prevents moisture from escaping from the wall, leading to blistering, hollowing, and peeling over long-term use. Increasing pores to improve breathability, on the other hand, reduces both waterproofing and water resistance. Furthermore, existing technologies require the addition of waterproofing and mildew-proofing agents to achieve moisture protection, which presents problems such as easy leaching of additives and insufficient stability.

[0005] Therefore, developing a damping coating that can balance waterproof and breathable properties has become a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0006] To overcome the shortcomings of the prior art, such as the difficulty in achieving both waterproofing and breathability, and the tendency to blister and peel, the present invention provides a composite coating for buildings. Another object of the present invention is to provide a method for preparing composite coatings for building applications; Another object of the present invention is to provide an application of a composite coating for building.

[0007] To solve the above-mentioned technical problems, the technical solution of the present invention is as follows: A composite coating for building applications comprises the following components by weight: 30-50 parts of an aqueous polymer matrix, 15-30 parts of a damping elastomer, 8-20 parts of a thermal insulation dispersed phase, 1.2-3.5 parts of a bio-based composite component, and 10-25 parts of water; wherein the bio-based composite component is composed of Eucommia ulmoides bark extract, silk protein peptides, and microbial fermented extracellular polysaccharides in a weight ratio of 1:0.6-0.8:0.3-0.5.

[0008] Preferably, the waterborne polymer matrix is ​​at least one of waterborne polyurethane emulsion and waterborne acrylic emulsion.

[0009] Preferably, the waterborne polyurethane emulsion has a solid content of 35-42 wt%, and the waterborne acrylic emulsion has a solid content of 36-45 wt%, and is used as a film-forming substrate for coatings.

[0010] Preferably, the damping elastomer is at least one of styrene-butadiene latex, water-based butyl latex, and chloroprene latex.

[0011] Preferably, the styrene-butadiene rubber latex content is 42-50 wt%, the waterborne butyl rubber latex content is 39-46 wt%, and the chloroprene rubber latex content is 41-49 wt%, providing viscoelastic damping for the coating.

[0012] Preferably, the heat-insulating dispersed phase is selected from at least one of hollow glass microspheres and fumed silica.

[0013] Preferably, the hollow glass microspheres have a particle size of 20-80 μm and the fumed silica has a specific surface area of ​​150-300 m². 2 / g, to regulate the pore structure and thermal insulation performance of the coating.

[0014] Furthermore, the bio-based composite component is a pre-emulsified aqueous dispersion with a solid content of 15-25 wt% and a particle size distribution D50 of 0.2-0.8 μm.

[0015] Preferably, 0.1~0.3 wt% Tween 80 is added for emulsification.

[0016] Preferably, the solid content is 18~22wt% and the particle size distribution D50 is 0.3~0.6 μm.

[0017] This invention utilizes the amphiphilic molecular structure of silk fibroin peptides and microbial fermented extracellular polysaccharides as natural polymeric emulsifying stabilizers. It achieves self-emulsification by encapsulating Eucommia ulmoides bark extract through hydrogen bonding of ternary components, eliminating the need for additional small-molecule surfactants / emulsifiers. Furthermore, the Eucommia ulmoides bark extract contains ≥75% total lignans by mass, with a number-average molecular weight of 8000~15000 Da and an acid value of 30~50 mg KOH / g; the lignans comprise lignan structural units bonded to the natural polysaccharide backbone.

[0018] Preferably, the total lignan content in the Eucommia ulmoides bark extract is 78%–85%, and the acid value is 35–45 mg KOH / g. Further, the Eucommia ulmoides bark extract is prepared by the following method: dried Eucommia ulmoides bark is pulverized and subjected to low-temperature hot air inactivation treatment at 40–50°C; reflux extraction is performed using a 70–80 wt% ethanol aqueous solution; the extract is filtered to remove solid residue; the filtrate is concentrated by vacuum distillation and then purified; molecular weight fractionation is performed by gel permeation chromatography; the target fraction is collected and dried to obtain the Eucommia ulmoides bark extract.

[0019] Furthermore, the silk protein peptides are low molecular weight peptides obtained by enzymatic hydrolysis of silk protein, with a number average molecular weight of 2000~5000 Da and a solid content of ≥90%.

[0020] Preferably, the number-average molecular weight of the silk protein peptide is 2500~4000 Da.

[0021] Furthermore, the extracellular polysaccharide produced by microbial fermentation is a lipopeptide-polysaccharide complex with a number-average molecular weight of 1~5×10⁻⁶. 6 Da.

[0022] Preferably, the number-average molecular weight of the microbial fermented extracellular polysaccharide is 1.5~3×10⁻⁶. 6 Da.

[0023] Furthermore, the microbial fermented extracellular polysaccharide is prepared by Bacillus subtilis through liquid fermentation at a temperature of 30-35°C for 48-72 h. The fermentation broth is centrifuged to remove the bacterial precipitate, and the supernatant is concentrated by ultrafiltration and freeze-dried to obtain the lipopeptide-polysaccharide complex.

[0024] Preferably, the liquid fermentation uses enzymatic hydrolysate of Eucommia bark extract by-product as the main component of the culture medium.

[0025] Furthermore, the bio-based composite component is prepared by the following method: Eucommia bark extract, silk protein peptide, and microbial fermented extracellular polysaccharide are mixed to form a composite material, and then the composite material is mixed with water at a mass ratio of 1:3~6 and dispersed evenly to obtain the bio-based composite component.

[0026] Preferably, the composite material is mixed with water at a mass ratio of 1:4 to 5.

[0027] A method for preparing the aforementioned composite coating for building use includes the following steps: S1. Add the water-based polymer matrix and damping elastomer to the water and stir and disperse at 25~35℃ for 20~40 min; S2. Add the bio-based composite components, keep warm and stir for 15-30 minutes to ensure the components are fully compatible and dispersed; S3. Add the heat-insulating dispersed phase to the system, continue stirring and dispersing for 25-40 min, and then let it stand for 30-60 min after defoaming and viscosity adjustment to obtain the composite coating for building.

[0028] An application of the aforementioned composite coating for building, wherein the composite coating is disposed between a floor slab and a surface material.

[0029] This invention constructs a coating system that combines a viscoelastic damping network and a regular microporous structure by compounding Eucommia bark extract, silk protein peptides and microbial fermented extracellular polysaccharides in a specific ratio and limiting their preparation and physical properties. This overcomes the inherent contradiction between sound insulation, breathability and waterproofing in conventional sound insulation coatings.

[0030] In terms of sound insulation, the bio-based composite components, through molecular chain entanglement and interfacial synergy, form a viscoelastic damping structure with a high loss factor, which can efficiently dissipate the low-frequency impact vibration energy of the floor slab and significantly reduce impact sound transmission. Conventional damping coatings often improve sound insulation performance by increasing coating density or adding rigid fillers, but this easily leads to increased coating brittleness and denser microporous structure, thereby weakening breathability and disrupting the balance of waterproof performance. This invention, through the synergistic effect of flexible bio-based components, increases damping internal loss without significantly increasing coating rigidity, achieving excellent low-frequency sound insulation while maintaining coating flexibility and film-forming stability.

[0031] Regarding breathability and waterproofing, this invention achieves a fine, uniformly distributed microporous structure by regulating the interfacial compatibility and film-forming behavior of the bio-based components. The tortuous distribution of micropores allows for the slow permeation of gaseous water vapor, ensuring the breathability of the coating. Simultaneously, the high overall density of the coating, without significant large interconnected pores, effectively resists the penetration of liquid water, achieving a synergistic optimization of breathability and waterproofing performance. Conventional coatings often excessively seal micropores to improve waterproofing, leading to decreased breathability and easy blistering and peeling of the coating; conversely, ensuring breathability often results in insufficient coating density and poor impermeability. This invention, through the precise regulation of the film-forming process by the bio-based components, achieves a dynamic balance between breathable channels and waterproof barriers at the microscopic scale, overcoming the mutual exclusion of their properties.

[0032] Compared with the prior art, the beneficial effects of the technical solution of the present invention are: The weighted normalized impact sound pressure level L of the composite coating of this invention n,w(CI) can reach 62 dB, with outstanding impact sound insulation effect in the low-to-mid frequency range of 160~400 Hz, significantly better than ordinary concrete floor slabs and conventional damping coatings, and possessing excellent floor vibration reduction and noise reduction capabilities. The composite coating of this invention has a water vapor permeability of up to 145 g / (m²). 2 • 24 h) can ensure that the moisture inside the wall can be discharged smoothly, avoiding coating blistering, hollowing and peeling; at the same time, the maximum impermeable water pressure can reach 0.30 MPa, which has excellent water penetration resistance and can achieve good waterproof effect without the need to add additional waterproofing agent. Detailed Implementation

[0033] The present invention will be further described below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in this technical field.

[0034] Unless otherwise specified, all reagents and materials used in the following examples are commercially available.

[0035] Waterborne polyurethane emulsion solid content 35-42 wt%, waterborne acrylic emulsion solid content 36-45 wt%; styrene-butadiene rubber latex solid content 42-50 wt%, waterborne butyl rubber latex solid content 39-46 wt%, chloroprene rubber latex solid content 41-49 wt%; hollow glass microspheres particle size 20-80 μm, fumed silica specific surface area 15-300 m² 2 / g. Bacillus subtilis is the standard strain CMCC(B)63501.

[0036] The lignans in the Eucommia bark extract include lignan structural units bonded to a natural polysaccharide backbone.

[0037] Example 1 1. Raw material preparation (1) Preparation of Eucommia bark extract Dried Eucommia ulmoides bark was pulverized in a pulverizer and passed through a 40-mesh sieve to obtain coarse Eucommia ulmoides bark powder. The coarse powder was placed in a hot air oven and kept at 45℃ for 60 min to inactivate endogenous enzymes. A 75 wt% ethanol aqueous solution was added at a material-to-liquid ratio of 1:10 (g:mL), and the mixture was heated to reflux temperature and refluxed for 2 h. This extraction was repeated twice, and the extracts were combined. The extract was filtered through filter paper to remove solid residues. The filtrate was distilled under reduced pressure at 55℃ and -0.08 MPa until no alcohol odor remained, yielding a concentrated solution. The concentrated solution was reconstituted with water and defatted by petroleum ether extraction. The aqueous phase was collected and dried under reduced pressure to obtain a crude extract. The crude extract was purified by gel permeation chromatography to remove impurities. The main eluent was collected and dried under reduced pressure to obtain Eucommia ulmoides bark extract (total lignan content 82%, number average molecular weight 12000 Da, acid value 40 mgKOH / g).

[0038] (2) Preparation of silk protein peptides Silk fibroin was prepared into a 10 wt% dispersion by adding deionized water, and the pH was adjusted to 7.0–7.5 using citric acid / sodium citrate buffer. Trypsin was added at a concentration of 1.5 wt% of the silk fibroin mass, and enzymatic hydrolysis was carried out at 45 °C for 3 h. After hydrolysis, the temperature was raised to 90 °C and incubated for 10 min to inactivate the enzyme. After cooling, the insoluble matter was removed by centrifugation. The supernatant was concentrated by nanofiltration and dried under reduced pressure at -0.09 MPa and 50 °C to obtain silk fibroin peptides (number average molecular weight 3000 Da, solid content 92%).

[0039] (3) Preparation of extracellular polysaccharides by microbial fermentation The defatted residue after extracting Eucommia bark was washed, pulverized, and then suspended in water. A complex of cellulase and hemicellulase was added for enzymatic hydrolysis to obtain the Eucommia residue hydrolysate. A small amount of phosphate was added to adjust the pH to 7.0-7.2 to form the fermentation medium. Activated Bacillus subtilis CMCC(B)63501 seed culture was inoculated into the fermentation medium at a rate of 5 vol%, and fermented at 32℃ and 200 rpm for 60 h. After fermentation, the fermentation broth was centrifuged at 8000 rpm for 20 min to remove bacterial cells, and the supernatant was collected. The supernatant was concentrated by 100 kDa ultrafiltration, dialyzed against deionized water for desalination, and freeze-dried for 48 h to obtain a lipopeptide-polysaccharide complex (molecular weight 2 × 10⁻⁶). 6 Da).

[0040] (4) Preparation of bio-based composite aqueous dispersion Eucommia bark extract, silk protein peptides, and microbial fermented extracellular polysaccharides were mixed at a weight ratio of 1:0.7:0.4 to obtain a complex material. Deionized water was added at a mass ratio of complex material to water of 1:4.5, and the mixture was dispersed at 6000 rpm for 20 min using a high-shear disperser to form a stable pre-emulsified aqueous dispersion (solid content 20 wt%, particle size D50 = 0.4 μm).

[0041] 2. Preparation of Composite Coatings for Building Use Prepare according to the following parts by weight: 40 parts of water-based polymer matrix, 22 parts of damping elastomer, 14 parts of heat-insulating dispersed phase, 2.2 parts of bio-based composite component, and 18 parts of water.

[0042] Add waterborne acrylic emulsion and styrene-butadiene latex to water and stir and disperse at 30°C for 30 min; add bio-based composite components and keep warm and stir for 20 min until fully dispersed; add hollow glass microspheres and continue stirring and dispersing for 30 min; after defoaming and viscosity adjustment, let stand and mature for 45 min to obtain a composite coating for building.

[0043] Example 2 The technical solution of Embodiment 2 is similar to that of Embodiment 1, with the following specific differences: The bio-based composite component consists of Eucommia ulmoides bark extract, silk fibroin peptides, and microbial fermented extracellular polysaccharides in a weight ratio of 1:0.6:0.3, with a solid content of 15wt% and a D50 of 0.2 μm. The Eucommia ulmoides bark extract has a number-average molecular weight of 8000 Da and an acid value of 30 mg KOH / g; the silk fibroin peptides have a number-average molecular weight of 2000 Da; and the microbial fermented extracellular polysaccharides have a molecular weight of 1×10⁻⁶. 6 Da.

[0044] Prepare according to the following parts by weight: 30 parts of water-based acrylic emulsion, 15 parts of water-based butyl latex, 8 parts of fumed silica, 1.2 parts of bio-based composite component, and 10 parts of water.

[0045] Example 3 The technical solution of Example 3 is similar to that of Example 1, with the following specific differences: The bio-based composite consists of Eucommia ulmoides bark extract, silk fibroin peptides, and microbial fermented extracellular polysaccharides in a weight ratio of 1:0.8:0.5, with a solid content of 25wt% and a D50 of 0.8 μm. The Eucommia ulmoides bark extract has a number-average molecular weight of 15000 Da and an acid value of 50 mg KOH / g; the silk fibroin peptides have a number-average molecular weight of 5000 Da; and the microbial fermented extracellular polysaccharides have a molecular weight of 5 × 10⁻⁶. 6 Da.

[0046] Prepare according to the following parts by weight: 50 parts of water-based acrylic emulsion, 30 parts of water-based butyl latex, 20 parts of fumed silica, 3.5 parts of bio-based composite component, and 25 parts of water.

[0047] Example 4 The technical solution of Example 4 is similar to that of Example 1, except that the mass ratio of the compound material to water in the preparation process of the bio-based composite component is 1:2.

[0048] Example 5 The technical solution of Example 5 is similar to that of Example 1, except that the solid content of the bio-based composite component water dispersion is 28wt% and the particle size D50 is adjusted to 1 μm.

[0049] Example 6 The technical solution of Example 6 is similar to that of Example 1, except that the fermentation medium for microbial fermentation of extracellular polysaccharides is replaced with a conventional glucose, yeast powder, and peptone complex medium.

[0050] Example 7 The technical solution of Example 7 is similar to that of Example 1, except that the fermentation conditions for microbial fermentation of extracellular polysaccharides are a fermentation temperature of 25°C and a fermentation time of 72 h; and Bacillus subtilis is replaced with Lactobacillus plantarum.

[0051] Example 8 The technical solution of Example 8 is similar to that of Example 1, except that the total mass content of lignans in the Eucommia bark extract is 80% and the acid value is 55 mg KOH / g.

[0052] Example 9 The technical solution of Example 9 is similar to that of Example 1, except that the number-average molecular weight of the silk fibroin peptide is 1800 Da and the molecular weight of the microbial fermented extracellular polysaccharide is 0.8 × 10⁻⁶. 7 Da.

[0053] Example 10 The technical solution of Example 10 is similar to that of Example 1, except that the fermentation temperature of Bacillus subtilis is 35°C and the fermentation time is 80 h.

[0054] Example 11 The technical solution of Example 11 is similar to that of Example 1, except that, during the preparation of the coating, an aqueous polymer matrix and a damping elastomer are added to water and stirred and dispersed at 50°C for 30 min.

[0055] Comparative Example 1 The technical solution of Comparative Example 1 is similar to that of Example 1, but without the addition of bio-based composite components.

[0056] Comparative Example 2 The technical solution of Comparative Example 2 is similar to that of Example 1, but in the bio-based composite component, the Eucommia bark extract is replaced with the bamboo extract.

[0057] Comparative Example 3 The technical solution of Comparative Example 3 is similar to that of Example 1, but in the bio-based composite component, silk protein peptides are replaced with fish collagen peptides.

[0058] Comparative Example 4 The technical solution of Comparative Example 4 is similar to that of Example 1, but in the bio-based composite component, the microbial fermentation extracellular polysaccharide is replaced with xanthan gum.

[0059] Comparative Example 5 The technical solution of Comparative Example 5 is similar to that of Example 1, except that the weight ratio of Eucommia bark extract, silk protein peptide, and microbial fermented extracellular polysaccharide is 1:1:1.

[0060] Comparative Example 6 The technical solution of Comparative Example 6 is similar to that of Example 1, except that the weight of the added bio-based composite component is 6 parts.

[0061] Comparative Example 7 The technical solution of Comparative Example 7 is similar to that of Example 1, except that when preparing the coating, after adding the water-based polymer matrix and the damping elastomer to the water and dispersing them evenly, the heat-insulating dispersion phase is added first and stirred and dispersed, and then the bio-based composite component is added and stirred and dispersed again.

[0062] Performance testing 1. Physical, chemical and sound insulation damping properties The tests were conducted in accordance with T / GDTL018-2023 "Technical Specification for Sound Insulation Coatings in Buildings" and GB / T 50121-2005 "Evaluation Standard for Sound Insulation in Buildings". The specimen structure was: 10mm floor tile + 30mm thick dry-hardened mortar + 5mm damping coating + 120mm thick reinforced concrete floor slab.

[0063] L of the reference bare plate and all samples n,w All measurements were calculated according to GB / T 50121-2005 "Standard for Evaluation of Building Sound Insulation"; among them, the L of the sample n,w The impact sound spectrum correction factor CI is further superimposed, which is the value of L in the examples and comparative examples in Table 3. n,w (CI).

[0064] Impact sound improvement ΔL n,w =L n,w Reference bare plate - L n,w For the sample, a positive value indicates that the sample's sound insulation performance is better than the reference bare board, and the larger the value, the more significant the improvement effect.

[0065] 2. Breathable and waterproof performance The water vapor transmission rate was determined according to GB / T 17146-2015 "Test Method for Water Vapor Transmission Performance of Building Materials and Their Products"; the water impermeability was determined according to GB / T 19250-2013 "Polyurethane Waterproof Coatings".

[0066] Analysis and Explanation (1) Basic physicochemical properties The composite coatings prepared in the embodiments of this invention meet the requirements of T / GDTL018-2023 in all basic physical and chemical properties. Their container state, workability, drying time, water resistance, alkali resistance, bond strength, environmental protection, and flame retardant properties are all excellent and similar. The test results of Example 1 are shown in Table 1.

[0067] Table 1. Test results of physicochemical properties and sound insulation and damping performance of Example 1

[0068] (2) Sound insulation performance As shown in Table 2, Example 1 exhibits good impact noise suppression capability within the frequency range of 63~5000 Hz. Based on GB / T 50121-2005, the L value of Example 1 was calculated using the above frequency data. n,w (CI) is 62 dB. Under the same test conditions, the reference bare concrete slab L n,w The weighted impact sound pressure level (CI) is 78 dB. Compared to the baseline floor slab, the composite coating of this invention reduces the weighted impact sound pressure level by 16 dB, effectively improving the floor slab damping and overall impact sound insulation performance.

[0069] Table 2 Sound insulation performance test results of Example 1

[0070] As shown in Table 3, the sound insulation performance comparison results indicate that the present invention achieves efficient dissipation and attenuation of impact sound from floor slabs through specific compounding relationships and optimized ratio ranges. In Example 4, the solid-liquid dispersion ratio of the system was unbalanced, the wetting and dispersion effect of the bio-based components in the system deteriorated, the uniform entanglement between molecules and the interfacial compatibility were slightly weakened, and it was difficult to form a regular and continuous damping microstructure after film formation. In Example 5, the density of particle packing and the interfacial contact state of the dispersion changed, the energy consumption of particle slippage and the damping effect of the microfacial interface were weakened. In Example 6, the monomer composition, branching structure and hydrogen bonding ability of the extracellular polysaccharide were changed, and it was impossible to form a flexible cross-linked framework equivalent to the optimal solution. In Examples 7 and 9, the process and raw material parameters were changed, which affected the construction of long-chain flexible molecular framework, the dispersion and molecular entanglement ability of components decreased, and the formation of continuous flexible cross-linked network was limited. In Example 8, the types and proportions of active functional groups contained in the Eucommia bark extract changed, and the hydrogen bonding and interfacial anchoring effects with protein peptides and polysaccharides were weakened. Example 10: The fermentation time was too long, resulting in local degradation of the extracellular polysaccharide molecular chains, weakening of hydrogen bonding association of the ternary biological components, damage to the continuity of the damping network, and a slight decrease in sound insulation effect. Example 11: The stirring temperature was too high during the preparation stage, resulting in slight demulsification and aggregation of the polymer emulsion, uneven dispersion of biological components, increased local interface defects inside the coating, and decreased damping loss.

[0071] Comparative Example 1: The coating relies solely on ordinary resin and fillers to form a film, lacking a specific flexible damping molecular network. It relies only on rigid fillers for passive sound insulation, lacking viscoelastic deformation energy dissipation capabilities and failing to effectively dissipate impact vibrations from the floor structure. Therefore, its sound insulation performance deteriorates the most. Comparative Example 2: Ordinary plant extracts lack the high content of phenylpropane-type lignans (open-ring isolar resins) specific to Eucommia ulmoides, resulting in phenolic hydroxyl side chain groups. This prevents them from forming specific hydrogen bond crosslinks with protein peptides and polysaccharides, leading to a lack of interfacial compatibility and interfacial damping effects, insufficient damping network integrity, and a significant decrease in sound insulation performance. Comparative Example 3: Fish collagen is mainly composed of rigid α-helical long peptides, lacking the highly flexible β-sheet short chain structure unique to silk peptides. It cannot interweave and entangle in the molecular gaps of the polymer matrix, lacking the structural basis for slip deformation. It is difficult to dissipate vibrational energy through chain segment friction, resulting in insufficient stress relaxation and damping energy dissipation, thus deteriorating sound insulation performance. Comparative Example 4: Xanthan gum only has thickening and rheological effects, lacking long-chain flexible cross-linking and viscoelastic damping properties. It cannot construct a continuous and deformable energy-dissipating framework, only playing a conventional thickening role without contributing to damping. Comparative Example 5: The ratio of the three biological raw materials is severely unbalanced, failing to construct a complete multi-point hydrogen-bonded cross-linked damping framework. The degree of molecular chain entanglement is significantly reduced, and the material's internal friction is significantly decreased. Comparative Example 6: Excessive addition of bio-based components results in excess bio-based components remaining free in the coating system. Drying shrinkage produces a large number of defective pores, disrupting the continuity of the damping structure and further deteriorating the sound insulation performance. Comparative Example 7: The feeding order is reversed, causing the thermal insulation filler to agglomerate prematurely. The bio-based components cannot uniformly coat the filler particles, increasing interfacial voids and further reducing viscoelastic energy dissipation efficiency.

[0072] Table 3 Comparison of sound insulation performance

[0073] (3) Breathable and waterproof performance As shown in Table 4, the composite coating prepared in Example 1 has a water vapor permeability of 145 g / (m²). 2 • 24 h), the impermeability can reach 0.30 MPa with the maximum impermeable water pressure gauge, which can achieve a synergistic balance between air permeability and waterproof performance, ensuring that indoor water vapor can be normally permeated and discharged, while effectively blocking the infiltration of external moisture.

[0074] Example 8 altered the surface polarity and hydrophilic interface characteristics of the Eucommia ulmoides bark extract, slightly weakening interfacial bonding during film formation and affecting the uniformity of micropore distribution, but without causing significant pore defects. Example 6 directly altered the polysaccharide monomer composition, molecular branching degree, and hydrophilic group content, reducing molecular chain regularity and making the film formation prone to local micropores and interfacial gaps. Example 7 caused a slight shift in the polysaccharide molecular weight distribution and the proportion of surface hydrophilic functional groups, reducing interfacial compatibility with other components. Example 9 resulted in an imbalance between the length and entanglement of polysaccharide molecular chain segments, failing to effectively fill the gaps between coating particles. Furthermore, changes in protein molecular chain flexibility and space-filling ability weakened the effect of filling micropores within the coating, slightly increasing pore connectivity. This weakened the appropriate air permeability control ability and reduced the coating's density and water-impermeability. Example 10, with its long fermentation time, caused partial degradation of the polysaccharide, slightly reducing the ability to control micropore formation, slightly worsening micropore uniformity, slightly increasing water vapor permeability, and slightly decreasing water-impermeable pressure.

[0075] The substitute raw materials in Comparative Examples 2 and 3 lack the corresponding characteristic polar structures and interfacial compatibility, making it impossible to finely control the micropore morphology and density of the coating film, resulting in significant pore defects. Xanthan gum in Comparative Example 4 only has rheological thickening effects and lacks the structural characteristics of the polysaccharide in this invention for regulating film-forming pores and optimizing interfacial bonding, thus it cannot participate in the construction of a dense and breathable coating skeleton.

[0076] Table 4 Breathability and Waterproof Performance

[0077] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A composite coating for building applications, characterized in that, The composition comprises the following components by weight: 30-50 parts of aqueous polymer matrix, 15-30 parts of damping elastomer, 8-20 parts of heat-insulating dispersed phase, 1.2-3.5 parts of bio-based composite component, and 10-25 parts of water; wherein the bio-based composite component is composed of Eucommia ulmoides bark extract, silk protein peptide, and microbial fermented extracellular polysaccharide in a weight ratio of 1:0.6-0.8:0.3-0.

5.

2. The composite coating for building applications according to claim 1, characterized in that, The bio-based composite component is a pre-emulsified aqueous dispersion with a solid content of 15-25 wt% and a particle size distribution D50 of 0.2-0.8 μm.

3. The composite coating for building applications according to claim 1, characterized in that, The total mass content of lignans in the Eucommia bark extract is ≥75%, the number average molecular weight is 8000~15000 Da, and the acid value is 30~50 mg KOH / g; the lignans include lignan structural units bonded to the natural polysaccharide backbone.

4. The composite coating for building applications according to claim 3, characterized in that, The Eucommia ulmoides bark extract was prepared by the following method: dried Eucommia ulmoides bark was pulverized and subjected to low-temperature hot air inactivation treatment at 40-50℃; it was extracted by reflux with 70-80wt% ethanol aqueous solution, and the extract was filtered to remove solid residue; the filtrate was concentrated by vacuum distillation and then purified, and molecular weight fractionation was performed by gel permeation chromatography, the target fraction was collected and dried to obtain the Eucommia ulmoides bark extract.

5. The composite coating for building applications according to claim 1, characterized in that, The silk protein peptides are low molecular weight peptides obtained by enzymatic hydrolysis of silk protein, with a number average molecular weight of 2000~5000 Da and a solid content of ≥90%.

6. The composite coating for building applications according to claim 1, characterized in that, The extracellular polysaccharide produced by microbial fermentation is a lipopeptide-polysaccharide complex with a number-average molecular weight of 1~5×10⁻⁶. 6 Da.

7. The composite coating for building applications according to claim 6, characterized in that, The microbial fermented extracellular polysaccharide was prepared by Bacillus subtilis through liquid fermentation at a temperature of 30-35°C for 48-72 h. The fermentation broth was centrifuged to remove the bacterial precipitate, and the supernatant was concentrated by ultrafiltration and freeze-dried to obtain the lipopeptide-polysaccharide complex.

8. The composite coating for building applications according to claim 1, characterized in that, The bio-based composite component is prepared by the following method: Eucommia bark extract, silk protein peptides, and microbial fermented extracellular polysaccharides are mixed to form a composite material, and then the composite material is mixed with water at a mass ratio of 1:3~6 and dispersed evenly to obtain the bio-based composite component.

9. A method for preparing a composite coating for building applications according to any one of claims 1 to 8, characterized in that, Includes the following steps: S1. Add the water-based polymer matrix and damping elastomer to the water and stir and disperse at 25~35℃ for 20~40 min; S2. Add the bio-based composite components, keep warm and stir for 15-30 minutes to ensure the components are fully compatible and dispersed; S3. Add the heat-insulating dispersed phase to the system, continue stirring and dispersing for 25-40 min, then defoam and adjust the viscosity, and let it stand for 30-60 min to obtain the composite coating for building.

10. The application of a composite coating for building as described in any one of claims 1 to 8, characterized in that, The building composite coating is applied between the floor slab and the surface material.

Citation Information

Patent Citations

  • Thermal-insulation damping coating used for buildings, and preparation method thereof

    CN106947346A